Women and the Gothic : an Edinburgh companion - Horner, Avril, 1947-; Zlosnik, Sue, 1949- (Edinburgh companions to the gothic., 2017)
A re-assessment of the Gothic in relation to the female, the 'feminine', feminism and post-feminism, this collection of newly commissioned essays brings together major scholars in the field of Gothic studies in order to re-think the topic of 'women and the Gothic'.